Thermal Effects of Vertical Greening in Summer: An Investigation on Evapotranspiration and Shading of Façade Greening in Vienna - Tarja Salonen; Jutta Hollands; Eldira Sesto; Azra Korjenic (Buildings, 2022)
Global urbanization is advancing, and with it, the densification of cities. Due to increased sealing of open spaces and the re-densification of existing urban settings, green spaces in the city are becoming scarcer. At the same time, greening within the urban fabric is known for its positive effects on the environment and decisively counteracts the urban heat effect. This study deals with the benefits of green façades for the environment as a cooling measure. Two façade greening systems, one trough and one cassette system, consisting of curtain wall elements with a basic metal structure, installed at a south-facing outdoor wall of a school building in Vienna, Austria, were taken under metrological examination. In order to evaluate the cooling effect caused by evapotranspiration, the amount of water evaporated was calculated using the difference of inflow and outflow. Furthermore, the surface temperatures of the greened and non-greened walls were measured to display the influence of the interaction of shading and evapotranspiration on the surrounding microclimate. The investigated vertical greening system with an area of 58 m2 has an average evaporation capacity of 101.38 L per day in the summer. The maximum surface temperature difference was measured to be 11.6 °C.